Creating timesheets in electronic format - Чиж, Александр Иванович (Eastern-European Journal of Enterprise Technologies, 2010)
There is researched possibility of creating and using programs to build timesheets for salary accounting in an electronic form in the environment of Visual Foxpro v. 9.0.